Seroprevalence of anti-influenza antibodies in humans and characterization of seasonal influenza viruses isolated in Russia during the 2023–2024 flu season - Svetlana V. Svyatchenko; Nikita D. Boldyrev; Anastasia S. Panova; Natalia P. Kolosova; Kiunnei N. Shadrinova; Natalia I. Goncharova; Galina S. Onkhonova; Alina R. Muratova; Alexey V. Danilenko; Elena I. Danilenko; Andrey S. Gudymo; Natalia N. Vasiltsova; et al. (Archives of Virology, 2025)

Genetic diversity and expansion routes of the invasive zebra mussel Dreissena polymorpha in Eastern Europe - Oksana V. Travina; Yulia V. Bespalaya; Alexander V. Kondakov; Ilya V. Vikhrev; Olga V. Aksenova; Andrey S. Aksenov; Evgeniy S. Babushkin; Mikhail Yu. Gofarov; Yulia S. Kolosova; Alexander V. Kropotin; Irina S. Khrebtova; Artem A. Lyubas; et al. (Hydrobiologia, 2025)

The last refugia for a polar relict pollinator: isolates of Bombus glacialis on Novaya Zemlya and Wrangel Island indicate its broader former range in the Pleistocene - Grigory S. Potapov; Mikhail V. Berezin; Yulia S. Kolosova; Alexander V. Kondakov; Alena A. Tomilova; Vitaly M. Spitsyn; Alisa A. Zheludkova; Natalia A. Zubrii; Boris Yu. Filippov; Ivan N. Bolotov (Polar Biology, 2021)

Severe cases of seasonal influenza and detection of seasonal A(H1N2) in Russia in 2018–2019 - Natalia P. Kolosova; Tatyana N. Ilyicheva; Alexey V. Danilenko; Svetlana V. Svyatchenko; Natalia I. Goncharova; Julia A. Bulanovich; Polina Yu Torzhkova; Alexander G. Durymanov; Andrei S. Gudymo; Alexander N. Shvalov; Ivan M. Susloparov; Tatyana V. Tregubchak; et al. (Archives of Virology, 2020)

Comparative thermostability analysis of zoonotic and human influenza virus A and B neuraminidase - Vasily A. Evseenko; Svetlana V. Svyatchenko; Natalia P. Kolosova; Valentina L. Kovrizhkina; Vasiliy Y. Marchenko; Aleksander G. Durymanov; Natalia I. Goncharova; Alexander B. Ryzhikov (Archives of Virology, 2020)

Intranasal immunization of guinea pig with trivalent influenza antigen adjuvanted by Cyclamen europaeum tubers extract - Vasily A. Evseenko; Natalia P. Kolosova; Anderi S. Gudymo; Semion V. Maltsev; Julia A. Bulanovich; Nataliya I. Goncharova; Natalia V. Danilchenko; Vasiliy Y. Marchenko; Ivan M. Susloparov; Alexander B. Ryzhikov (Archives of Virology, 2019)

Humoral immunity to influenza in an at-risk population and severe influenza cases in Russia in 2016–2017 - Tatyana N. Ilyicheva; Alexander G. Durymanov; Svetlana V. Svyatchenko; Vasily Yu. Marchenko; Ivan A. Sobolev; Anastasiya Yu. Bakulina; Natalia I. Goncharova; Natalia P. Kolosova; Ivan M. Susloparov; Olga G. Pyankova; Alexander B. Ryzhikov; Rinat A. Maksyutov (Archives of Virology, 2018)

Beneficial effects of melatonin in a rat model of sporadic Alzheimer’s disease - Ekaterina A. Rudnitskaya; Kseniya Yi. Maksimova; Natalia A. Muraleva; Sergey V. Logvinov; Lyudmila V. Yanshole; Nataliya G. Kolosova; Natalia A. Stefanova (Biogerontology, 2015)

Association of AMD-like retinopathy development with an Alzheimer’s disease metabolic pathway in OXYS rats - Oyuna S. Kozhevnikova; Elena E. Korbolina; Natalia A. Stefanova; Natalia A. Muraleva; Yuriy L. Orlov; Nataliya G. Kolosova (Biogerontology, 2013)

Molecular mechanisms of cold-induced CYP1A activation in rat liver microsomes - Maria Perepechaeva; Natalia Kolosova; Alevtina Grishanova (Journal of Physiology and Biochemistry, 2011)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.